Optical Emission Spectroscopy Study using Plasma Jet System - Leelamohan, Pravind; Nayan, Nafarizal (Evolution in Electrical and Electronic Engineering, 2022)
Plasma is no longer an alien term used in various industries such as semiconductor, medical and many other industries. This project is done to observe, how the Optical Emission Spectroscopy method affects the plasma jet system. The spectrometer that gathers the spectrum emitted by the active plasma factorizes the plasma that is examined using Optical Emission Spectroscopy. The spectrum that is collected shows the characteristic of the plasma that is collected. The plasma is emitted using the Atmospheric pressure plasma needle jet (APPNJ). Then argon gas is flowed into the machine using a quartz tube and high voltage is supplied to the tube which is coated using copper foil. A neon transformer is used to step up the voltage as only high voltage can produce plasma. The composition of plasma is then emitted to justify the experiment as its effect of it will also be shown in comparison to the reading of the spectrometer. This project will be beneficial to the semiconductor industries as well as medical industries.